PEMBENTUKAN BINTARA PEMBINA POTENSI MARITIM DI POS ANGKATAN LAUT PERSPEKTIF HUKUM MARITIM - Mangisi Simanjuntak (Fakultas Hukum Universitas Kristen Indonesia, 2018)
Maritime is a source of energy, a source of food and as a source of wealth as well as means of transportation and defense media that must be developed and maintained and secured for the bene t of the nation and the people of Indonesia. For the development, defense and security of the maritime potential, it is necessary to increase all work units in the agencies engaged in maritime potential, especially the Navy outpost. However, all of them do not have personnel or Maritime Potential Builders who are able to sharpen the implementation of the tasks of fos- tering human resources and developing natural resources in maritime potential through social communication methods, fostering regional resilience and social services. Faced with the increasingly complex problems and the growing challenges of developing all the more effective maritime potential in achieving the goal of making Indonesia a global maritime axis. Keyword : maritime; defense and security; the Navy; natural resources.